Perkuliahan Online dengan Aplikasi WhatsApp dalam Program Belajar dari Rumah dimasa Pandemi Covid-19 Fakultas Dakwah Uin Sulthan Thaha Saifuddin Jambi - Ade Novia Maulana; Ahdiyat Mahendra (MAUIZOH: Jurnal Ilmu Dakwah dan Komunikasi, 2021)
The Covid-19 pandemic has forced humans to change behavior in various aspects and various fields, including education. The basic policy carried out by the government for the world of education during the Covid-19 Pandemic is the existence of a study from home policy for all levels of education. This policy changed the way educational institutions conduct the learning process, from face-to-face learning in the classroom to distance learning. Ready or not ready, the COVID-19 pandemic has forced universities that previously were not optimal in preparing and implementing online learning to carry out full implementation. Students and lecturers who previously lacked interest in carrying out online learning were required to conduct online lectures. Because the essence of lectures is a dialogue between students and lecturers or between students and students, then in the implementation of online lectures an application is needed that can guarantee the implementation of the dialogue. Of the many internet facilities for online lectures, the WhatsApp application is one of the recommended options for use in online lectures. The method used in this research is descriptive qualitative method. In collecting the data, this research conducted observations on the whatsapp group. While the data analysis technique of this research is descriptive qualitative. The results of this study are the whatsapp group feature is a good alternative used in the online learning process. There are so many benefits and also students become active in class even though they don't do face-to-face.